Degradation in vitro and in vivo of β-TCP/MCPM-based premixed calcium phosphate cement. (February 2019) - Shu, Yao; Zhou, Yu; Ma, Pengwei; Li, Chunge; Ge, Cheng; Wang, Ying; Li, Qihong; Yu, Kaitao; Lu, Rongjian; Zou, Xuan; Yin, Yuji; Li, Junjie
Abstract: Premixed calcium phosphate cements (CPCs) have been developed to shorten the surgical time of conventional CPCs. However, there is lack of investigation on degradation behavior of premixed CPCs in vitro and in vivo . In this study, the premixed CPCs are prepared by mixing glycerol or polyethylene glycol (PEG) with the CPC power (β-tricalcium phosphate (β-TCP) and monocalcium phosphate monohydrate (MCPM)), and their degradation performances including the microstructure, chemical composition and mechanical properties are systematically evaluated both in vitro and in vivo (subcutaneous implantations in rabbits). When the premixed CPCs aged in PBS or FBS, results show weight loss of the specimens, decreased pH value and increased calcium ion concentration of aging media. Meanwhile, the setting products convert from dicalcium phosphate dihydrate (DCPD) to dicalcium phosphate anhydrous (DCPA), and no hydroxyapatite deposit. The specimen size and the molecular weight of non-aqueous solvent can modulate the setting product of premixed CPCs. For the larger specimens, DCPA is the main setting product, for the smaller ones, the composite contained DCPD and DCPA. With the decrease of the molecular weight of the non-aqueous solvent PEG, the setting product change from both DCPD and DCPA to DCPA due to the quicker exchange rate of PEG with water. After a period of subcutaneous implantation, the surface of the grafts obviously disintegrated with the formation of porous structures, but their internal morphology do not obviously change. Highlights: This work prepared a premixed CPC using glycerol or polyethylene glycol (PEG) as the non-aqueous solvent. The degradation, mechanical behaviors and phase conversion in vitro of prepared premixed CPC were investigated. The properties of premixed CPC after subcutaneous implantation in rabbit were studied.